2021
DOI: 10.1097/qad.0000000000002747
|View full text |Cite
|
Sign up to set email alerts
|

Declines in HIV prevalence in female sex workers accessing an HIV treatment and prevention programme in Nairobi, Kenya over a 10-year period

Abstract: Objectives: Empirical time trends in HIV prevalence in female sex workers (FSWs) are helpful to understand the evolving HIV epidemic, and to monitor the scale-up, coverage, and impact of ongoing HIV prevention and treatment programmes. Design: Serial HIV prevalence study. Methods: We analyzed time trends in HIV prevalence in FSWs accessing services at seven Sex Worker Outreach Programme (SWOP) clinics in Nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Despite this, in Nairobi there has been no obvious increase in HIV/STBBI incidence to date. Whether this is due to natural decline [80] or COVID-19 is uncertain, and if the decrease is due to economic reasons, there could be an increase in incidence following economic recovery, which needs to be monitored carefully [81].…”
Section: Case Study 3: Kenyamentioning
confidence: 99%
“…Despite this, in Nairobi there has been no obvious increase in HIV/STBBI incidence to date. Whether this is due to natural decline [80] or COVID-19 is uncertain, and if the decrease is due to economic reasons, there could be an increase in incidence following economic recovery, which needs to be monitored carefully [81].…”
Section: Case Study 3: Kenyamentioning
confidence: 99%
“…The HIV epidemic among key populations (KP) shows geographical and gender diversity with self‐reported HIV prevalence among FSWs ranging from 49% in Homabay to 16% in Mombasa and 36% among female PWID to 17% among male PWID [8]. Newer studies from Nairobi [9] and Mombasa [10] report that HIV prevalence among FSWs decreased over time in all age groups. This decline is attributed by the researchers to the scale‐up of HIV prevention and treatment services in Kenya [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Newer studies from Nairobi [9] and Mombasa [10] report that HIV prevalence among FSWs decreased over time in all age groups. This decline is attributed by the researchers to the scale‐up of HIV prevention and treatment services in Kenya [9,10]. Another study conducted with MSM and transgender women in coastal Kenya between 2016 and 17 found that overall, HIV‐1 incidence was 5.1 (95% confidence interval (CI): 2.6 to 9.8) per 100 person‐years (PY) (men who had sex with men exclusively (4.5 per 100 PY)) and transgender women (20.6 per 100 PY) [11].…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved through the implementation of an aggressive strategy that prioritizes specific populations and geographic regions with high HIV prevalence and incidence (8). Kenya has a vibrant combination of HIV prevention programs that target key populations, with FSWs as a predominant priority population, and recent studies highlight significant progress in intervention uptake and the reduction of HIV prevalence among FSWs (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%